Wind characteristic analysis based on Weibull distribution of Al-Salman site, Iraq - Faleh H. Mahmood; Ali K. Resen; Ahmed B. Khamees (Energy Reports, 2020)
This paper aims to analyze the characteristic of wind speed data in Al-Salman site - Iraq using Weibull distribution. Maximum likelihood method (MLM) was used to find out two essential Weibull parameters. The best wind distribution was described by using probability density function and cumulative distribution function. Based on Weibull parameters, an analysis is carried out for various wind turbine hub heights. The characteristics of wind wave for this site are regular, uniform, and close to Rayleigh function. Furthermore, the shape factor and scale factor have fluctuated from 1.8 to 3.2 and from 5.93 m/s to 8.3 m/s for different period respectively. It was found that, at 50 m height, the mean wind speed is 5.93m/s, mean power density for this site is 219 W/m and that almost 50% of the wind speed was above 5 m/s within the total hours per annum. As consequence, this site has a potential wind power to erect small wind turbines for electricity production. Wind turbine model was proposed relying on capacity factor.
Keywords: 330; Weibull distribution; Maximum likelihood method; Wind turbine